Fatty acid composition of Edam, Emmental and Gouda cheeses produced in Slovenia in autumn 1997 - Mojca KOMAN RAJŠP; Vekoslava STIBILJ (Acta Agriculturae Slovenica)
The aim of our work was to determine fatty acid composition of three different types of cheeses - Edam, Gouda and Emmental, produced in Slovenia in autumn 1997. The analysed Edam and Gouda cheese was produced by three and Emmental cheese by two different producers. All samples were purchased in the local supermarkets twice in the period of three months in autumn 1997. The methyl esters of the fatty acids were prepared by in situ transesterification (ISTE) and determined by gas chromatography. The average total SAT (saturated fatty acids) content was 56.80 wt % (relative percentage for each fatty acid of the total fatty acids) for Emmental cheese, 56.62 wt % for Edam cheese and 57.49 wt % for Gouda cheese. The average total MUFA (monounsaturated fatty acids) content was 34.26 wt % for Emmental cheese, 34.28 wt % for Edam cheese and 33.45 wt % for Gouda cheese. The average total PUFA (polyunsaturated fatty acids) content was 5.30 wt % for Emmental cheese, 5.74% for Edam cheese and 5.64% for Gouda cheese. No great difference was found between three types of cheese concerning the fatty acid profile (wt %).